Evaporation and mixture formation characteristics of diesel spray under various nozzle hole size and injection pressure condition employing similar injection rate profile. (April 2021) - Safiullah,; Nishida, Keiya; Ogata, Youichi
Abstract: The current work demonstrates investigations of the effects of the nozzle hole size and injection pressure on the diesel spray under evaporating condition. Three single hole injectors with hole diameters of 0.101 mm, 0.122 mm and 0.133 mm were used and their injection rate profiles were shaped in a similar manner. Laser Absorption Scattering technique was implemented in the diesel spray experiments to visualize the vapor phase and measure the mixture concentration. Also, the experimental results were validated with the computational approach. The injection rate profile and initial spray trajectory angle are key inputs for the CFD simulation; thus, careful measurements were taken. The injection rate profiles were measured by Zeuch method and based on the start of injection with the High-speed Video camera frame, the 5 kHz Butterworth low pass filter was applied to the injection rate raw signal. Moreover, the near nozzle field microscopic spray imaging experiments were performed to measure the initial spray trajectory angle. The experimental results show that the 0.101 mm hole diameter injector promotes shorter liquid length, longer vapor length, higher evaporation ratio and higher entrained air mass. The computational results show a reasonable qualitative agreement with the experiments; however, a quantitative discrepancy can be noticed.